Faunistic Overview of Calanoid Copepods (Crustacea) from Continental Waters of Ukraine - Samchyshyna, L. (Вестник зоологии, 2011)
Faunistic overview together with updated checklist, comprising 38 species and 2 subspecies of calanoid copepods inhabiting fresh and brackish Ukrainian waters classified in three families and twelve genera is provided. The only freshwater calanoid species endemic to Ukraine is Speodiaptomus birsteini Borutzky, 1962, a stygobiont found once in an underground lake in the Skels’ka Cave (Crimean Peninsula). Two species, Hemidiaptomus (Hemidiaptomus) rylovi Charin, 1928 and S. birsteini are included as a threatened species in the Red Book of Ukraine. Dubious records and distribution patterns of some calanoid taxa are discussed. The calanoid fauna of Ukraine is compared with those of adjacent countries. Представлен фаунистический обзор с обновленным списком, состоящий из 38 видов и 2 подвидов, относящихся к трем семействам и двенадцати родам каланоидных копепод, обитающих в пресных и солоноватых водах Украины. Speodiaptomus birsteini Borutzky, 1962, единственный пресноводный вид каланоид эндемик Украины, стигобионт найденный однажды в Скельской пещере Крымского полуострова. Два вида Hemidiaptomus (Hemidiaptomus) rylovi Charin, 1928 и S. birsteini в настоящее время занесены в Красную книгу Украины. Обсуждаются распространение каланоидных копепод, а также сомнительные находки некоторых видов в Украине. Фауна каланоид Украины сравнивается с таковой соседних стран.